2017
DOI: 10.1016/j.pan.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the understanding and management of pain in chronic pancreatitis

Abstract: Abdominal pain is the foremost complication of chronic pancreatitis (CP). Pain can be related to recurrent or chronic inflammation, local complications or neurogenic mechanisms with corresponding changes in the nervous systems. Both pain intensity and the frequency of pain attacks have been shown to reduce quality of life in patients with CP. Assessment of pain follows the guidelines for other types of chronic pain, where the multidimensional nature of symptom presentation is taken into consideration. Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
237
0
53

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 258 publications
(293 citation statements)
references
References 118 publications
3
237
0
53
Order By: Relevance
“…10 Pain prevalence and pain patterns. Sixty percent of patients had pain, and intermittent pain was the most frequently reported pain pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Pain prevalence and pain patterns. Sixty percent of patients had pain, and intermittent pain was the most frequently reported pain pattern.…”
Section: Discussionmentioning
confidence: 99%
“…These include patients' age at diagnosis, 8 etiology and duration of CP, 8,9 morphological features of the pancreas including pancreatic duct pathology, 10 and the presence (or absence) of exocrine pancreatic insufficiency (EPI) and diabetes. These include patients' age at diagnosis, 8 etiology and duration of CP, 8,9 morphological features of the pancreas including pancreatic duct pathology, 10 and the presence (or absence) of exocrine pancreatic insufficiency (EPI) and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term beneficial effects of opioids on chronic pancreatitis pain are not proven; still, 50% of chronic pancreatitis patients use opioids on a daily basis [19]. Interestingly, pain relief can be achieved in a large proportion of these patients by treating their morphological abnormalities by interventional endoscopy or surgery [3, 20-23]. Bearing in mind that the longer patients are treated with opioids, the greater the risk of opioid dependence and opioid-induced hyperalgesia, it seems better to use opioids as a bridge to invasive treatment when morphological abnormalities are present instead of definitive treatment [3, 24].…”
Section: Step-up Approach For the Treatment Of Chronic Pancreatitis Painmentioning
confidence: 99%
“…In the current literature and guidelines for painful obstructive chronic pancreatitis, inconsistency is found regarding the timing and choice for surgery or endoscopy first [3, 23, 25]. Recently, multiple studies have suggested that early surgery is superior in providing pain relief and improvement of quality of life, compared to the step-up approach in which medical therapy is followed by endoscopy and finally surgery [4-6].…”
Section: Timing Of Surgery In Chronic Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation